A historical study of Zimbabwe’s African Elite: configurations, networks and transitions c.1900-2013 - Tarugarira, Gilbert (Midlands State University, 2017)
A Thesis by Dr Gilbert Tarugarira a Lecturer in the Department of Historical Studies, Midlands State University